The effect of intrinsic and extrinsic motivations on academics' entrepreneurial intention - Davide Antonioli; Francesco Nicolli; Laura Ramaciotti; Ugo Rizzo (Administrative Sciences, 2016)
This work investigates entrepreneurial intentions among academic scientists. Drawing from the literature on entrepreneurial behavior, it contributes to delineate the differences in motivations that are correlated with entrepreneurial intention to those that are considered to be linked to entrepreneurial behaviors. By disentangling the concept of motivations in its ultimately basic constructs of intrinsic and extrinsic motivations, we investigate how these two different types of motivations are related to the formation of entrepreneurial intention at the level of academic scientists. Through a survey conducted at the University of Ferrara-one of the leading universities in Italy in terms of technology transfer and scientific production-findings reveal that while academic entrepreneurial intention seems to be mostly driven by intrinsic motivations, the effect of extrinsic motivations, which are regarded as a main antecedent of entrepreneurial behavior among scientists, are largely mediated by academic positions, work environment and different combinations of these two factors. This work therefore highlights the importance of social norms in the investigation of entrepreneurial intention in academia.
Keywords: 350; intrinsic motivations; extrinsic motivation; entrepreneurial intention; academic entrepreneurship